Heterogeneity of response to methylphenidate in apathetic patients in the ADMET 2 Trial. (20th December 2022) - Lanctôt, Krista L.; Perin, Jamie; Vieira, Danielle; Rosenberg, Paul B.; Herrmann, Nathan; Shade, David; Lerner, Alan J.; Padala, Prasad R; Brawman‐Mintzer, Olga; van Dyck, Christopher H; Porsteinsson, Anton P.; Craft, Suzanne; et al.
Abstract: Background: Apathy is the most common neuropsychiatric symptom in Alzheimer's disease (AD), however there are no approved treatments. In the recent Apathy in Dementia Methylphenidate Trial 2 (ADMET 2), methylphenidate treatment resulted in a significant reduction in apathy with a small to medium effect size. Given these results and the clinical heterogeneity of apathetic AD patients, we assessed the heterogeneity of response to methylphenidate in ADMET 2 to identify individuals who may benefit particularly from this treatment. Method: In this multicenter, randomized, placebo‐controlled clinical trial of 177 AD patients with clinically significant apathy, participants were randomized to receive methylphenidate or placebo for 6 months. Twenty‐one unplanned potential predictors of treatment outcomes were assessed. Predictors were chosen for multivariate modeling based on estimated effect difference, difference of change in the Neuropsychiatric Inventory (NPI)‐apathy subscale of two or more at the 6 month visit. Participants were then grouped into 10 subgroups by their index scores, which were constructed based on the predictors with the biggest difference in effect. Result: Of the 21 predictors, six were chosen for multivariate modelling based on having an effect difference of 2 or more in the NPI apathy score. Four of these predictors had a significant interaction with the treatment. Methylphenidate was more effective in participants less likely to have baseline anxiety (‐3.1, 95% CI ‐5.7 ‐ ‐0.5, p = 0.023) or agitation (‐3.6, 95% CI ‐6.1 ‐ ‐1.1, p = 0.005) as measured by the NPI, taking a cholinesterase inhibitor (‐4.1, 95% CI ‐6.7 ‐ ‐1.3, p = 0.004), taking at least one AD medication (‐4.0, 95% CI ‐6.9 ‐ ‐1.1, p = 0.008), highly educated (‐2.1, 95% CI ‐5.4 – 1.3, p = 0.231), and low functional capacity (‐2.6, 95% CI ‐5.55 – 0.26, p = 0.076) as measured by the Activities of Daily Living scale. Conclusion: Individuals who were less anxious or agitated, more highly educated, on treatment for Alzheimer's disease, and with low functional capabilities were more likely to benefit from methylphenidate when compared to placebo. Consistent with its potential activating effects, methylphenidate may be particularly beneficial for subgroup of apathetic AD participants with lower baseline anxiety and agitation.